High-strength Neodymium Magnetic Beads: A Rare Foreign Body in the Bladder of an Adolescent() - Pieretti, Rafael V. (Urol Case Rep, 2014)
This article reports the case of an adolescent who repeatedly inserted high-strength magnetic beads into his urethra for erotic reasons. The beads migrated into his bladder requiring a cystostomy to remove them. The available literature is reviewed.